Outras paragens: paisagem e infância em Manuel da Fonseca - Costa, Carla Santos da (2016)
The present study proposed the reading of some of the short stories in Aldeia Nova (1942) and O Fogo e as Cinzas (1953) from the Portuguese writer Manuel da Fonseca. These analysis were developed under two principal interpretative plots: the representation of landscape and childhood. To do so, we had as pretension evaluate how the landscape, in the author’s narratives, acquires symbologies that link to the inseparable relation between the man and environment, his subjectivity and the physical space that surrounds him, relation that says much about the imaginary and the identity of these individuals. In a similar way we attend to the symbolic weight attributed to the infant characters and how they conceive the transit from childhood to grown up life, as well as the losses, the fears and frustrations. With this intention, we localize the production of Manuel da Fonseca in the social-historic context of Portugal in the beginning of the Twentieth century, having as initial point the imaginary of heroic greatness that borders all the Lusitanian history, until we come to the context of the Salazar dictatorship and its issues. Among them, the abandonment of small rural communities and the muting of these communities’ individuals, aspects that show up in Manuel da Fonseca’s writing as commitment, placing him in the context of Portuguese Neorealism intentions, with denunciations that, imbricated in his productions that distance the plots of his authorship from the problematic propagandistic writing.